Microwave Propagation in Rectangular Waveguide Containing Semiconductor Subject to Transverse Magnetic Field - Rahman, Syed (My University, 1968)
A detailed theoretical analysis of the propagation constant and the field components in rectangular waveguide completely filled with a semiconductor subjected to an external transverse applied magnetic field, has been carried out. A numerical solution of the transcendental equation for the propagation constant has been obtained for the n-type germanium samples with different conductivities and magnetic fields.
An experimental verification of this theoretical analysis has been made with a 22.2 ohm-em, n-type germanium sample at 9.46 GHz. The applied transverse magnetic field was varied from 0 to 10 Kilogauss. Measurements of the reflection co efficients at the air-semiconductor interface for different values of the applied magnetic field have been made with a high precision microwave reflection bridge. The experimental results agree well with the theoretical results.
Keywords: Microwave Propagation; Rectangular Waveguide; Semiconductor Subject; transverse Magnetic Field